2021
DOI: 10.1111/jrh.12562
|View full text |Cite
|
Sign up to set email alerts
|

State health disparities research in Rural America: Gaps and future directions in an era of COVID‐19

Abstract: Purpose In an era of the COVID‐19 pandemic, improving health outcomes for diverse rural communities requires collective and sustained actions across transdisciplinary researchers, intersectoral partners, multilevel government action, and authentic engagement with those who carry the burden—rural communities. Methods Drawing from an analysis of transcriptions and documents from a national workshop on the “State of Rural Health Disparities: Research Gaps and Recommendations,” this brief report underscores the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
1
20
0
3
Order By: Relevance
“…As this study suggests, depression was already a problem before the pandemic began in rural communities in the United States. Considering these findings, taken together with other research that has found severe economic impacts on rural areas due to the pandemic (Cacari Stone et al, 2021; Mueller et al, 2021) response and recovery policies must seek to reduce mental health inequities in rural communities, rather than seek to return these communities to their prepandemic depression status.…”
Section: Discussionmentioning
confidence: 85%
“…As this study suggests, depression was already a problem before the pandemic began in rural communities in the United States. Considering these findings, taken together with other research that has found severe economic impacts on rural areas due to the pandemic (Cacari Stone et al, 2021; Mueller et al, 2021) response and recovery policies must seek to reduce mental health inequities in rural communities, rather than seek to return these communities to their prepandemic depression status.…”
Section: Discussionmentioning
confidence: 85%
“…Rural Health introduces a keen set of challenges, most notably, often affecting the population's overall health and health outcomes. Due to a multitude of risk factors such as geographic isolation, lack of access to healthcare, lower socioeconomic status, and limited job opportunities, rural populations are subjected to lower health outcomes in comparison to their urban counterparts [34]. Rural communities tend to be older with more than 8 million people who are 65 years of age or older [35].…”
Section: Rural Healthmentioning
confidence: 99%
“…Rural communities tend to be older with more than 8 million people who are 65 years of age or older [35]. These populations are at a greater risk of dying from cancer, heart disease, accidental injury, chronic lower respiratory disease, and stroke [34,36]. Rurality accompanied by pre-existing comorbidities appears to significantly lower the health outcomes of rural Americans.…”
Section: Rural Healthmentioning
confidence: 99%
“…Rural areas account for nearly 20% of the US population and are increasingly diverse. 11 , 12 Residents in rural areas may experience a negative impact to their health and well‐being because of shortages of health care facilities and providers and higher rates of poverty. 11 , 13 , 14 Due to lack of high‐speed internet, limited access to providers, and lower health insurance rates, underserved patient populations who reside in rural areas face challenges receiving primary and contraceptive care.…”
Section: Introductionmentioning
confidence: 99%
“…FQHCs’ role in access to care is particularly important in rural America. Rural areas account for nearly 20% of the US population and are increasingly diverse 11,12 . Residents in rural areas may experience a negative impact to their health and well‐being because of shortages of health care facilities and providers and higher rates of poverty 11,13,14 .…”
Section: Introductionmentioning
confidence: 99%